2010
DOI: 10.1111/j.1750-3841.2009.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior of High‐Concentration Sodium Caseinate Dispersions

Abstract: The results of this study should be useful for creating new products with high concentrations of sodium caseinate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
5
8
0
Order By: Relevance
“…At high concentrations, the viscosity does not diverge as quickly as for the suspensions of droplets. This result is in agreement with previous studies on sodium caseinate, in which suspensions at higher concentrations were studied Farrer and Lips (1999); Pitkowski et al (2008); Loveday et al (2010). In these works, it was shown that the viscosity does not diverge but follows a power law η 0 /η s ∝ (φ ef f,prot ) 12 .…”
Section: Protein Suspensionssupporting
confidence: 93%
See 2 more Smart Citations
“…At high concentrations, the viscosity does not diverge as quickly as for the suspensions of droplets. This result is in agreement with previous studies on sodium caseinate, in which suspensions at higher concentrations were studied Farrer and Lips (1999); Pitkowski et al (2008); Loveday et al (2010). In these works, it was shown that the viscosity does not diverge but follows a power law η 0 /η s ∝ (φ ef f,prot ) 12 .…”
Section: Protein Suspensionssupporting
confidence: 93%
“…The viscosity behaviour of the suspensions they form is displayed inFigure 5.At high concentrations, the viscosity does not diverge as quickly as for the suspensions of droplets. This result is in agreement with previous studies on sodium caseinate, in which suspensions at higher concentrations were studied Farrer and Lips (1999); Pitkowski et al(2008);Loveday et al (2010). In these works, it was shown that the viscosity does not diverge but follows a power law η 0 /η s ∝ (φ ef f,prot ) 12 .The behaviour displayed by sodium caseinate resembles that of core-shell microgelsTan et al (2005) and soft spherical brushesVlassopoulos et al (2001), hence a soft colloid framework (as reviewed e.g.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…3. The obtained surface concentration of the dissolving particles, 98 kg•m −3 , corresponds well to the overlap concentration of sodium caseinate measured by Loveday et al (2010) and Pitkowski et al (2008). The linear dependence of (Hellborg et al 2012) is incorrect due to the usage of an inaccurate source for diffusion coefficient for sodium caseinate dissolution rate and k mt indicates that the resistance to dissolution solely is the hydrodynamics of the process, in accordance with Eq.…”
Section: Discussionsupporting
confidence: 79%
“…The casein micelles in the spray-dried milk powders retained a globular shape (diameter ~100 nm), whereas larger casein micelles (clusters) were present in rollerdried milk powder. Heat-induced aggregation was also reported for casein and sodium caseinate dispersions (HadjSadok et al, 2008;Loveday et al, 2010;Ono et al, 1999;Quo et al, 1989). loss modulus (G″) is defined as the relaxation time (τ).…”
Section: Characterization Of Calcium Caseinate Powdersmentioning
confidence: 62%